The Mixed Phase of Charged AdS Black Holes - Piyabut Burikham; Chatchai Promsiri (Advances in High Energy Physics)
We study the mixed phase of charged AdS black hole and radiation when the total energy is fixed below the threshold to produce a stable charged black hole branch. The coexistence conditions for the charged AdS black hole and radiation are derived for the generic case when radiation particles carry charge. The phase diagram of the mixed phase is demonstrated for both fixed potential and charge ensemble. In the dual gauge picture, they correspond to the mixed phase of quark-gluon plasma (QGP) and hadron gas in the fixed chemical potential and density ensemble, respectively. In the nuclei and heavy-ion collisions at intermediate energies, the mixed phase of exotic QGP and hadron gas could be produced. The mixed phase will condense and evaporate into the hadron gas as the fireball expands.